In Silico Study of Secondary Metabolite Compounds in Parsley (Petroselinum crispum) as a Drug Therapy for Blood Cancer (Myeloproliferative Neoplasm (MPN)) targeting JAK-2 - Rizky Prasiska Wulandari; Kevin Gabriel; Halwa Aulia Nurdin; Diffa Hauna F. Pakhrul; Sabiq Salmandhiya Harits; Natasya Prameswari; Alya Puteri Agustina Pribadi; Diah Lia Aulifa (Indonesian Journal of Chemical Science, 2023)
Myeloproliferative neoplasm (MPN) is a clonal hematopoietic stem cell disorder. A commonly found related gene mutation is a mutation of the JAK2 kinase, thus making it a potential MPN pharmacotherapeutic target. One such pharmacotherapeutic agent with this mechanism is Ruxolitinib, which has anemia and thrombocytopenia as side effects. Based on literature, the parsley herb has a potential as an anticancer. The activity of the secondary metabolites of parsley herb were tested on JAK2 in-silico, with the goal being to develop a potential MPN pharmacotherapeutic agent candidate with minimized side effects. This was done by redocking a native ligand (5-amino-3-[(4-cyanophenyl)amino]-N-phenyl-1H-1,2,4-triazole-1-carboxamide) and docking 15 test ligands which are secondary metabolites of parsley herb to JAK2. The Gridbox that was used is situated on x center : 10.06, y center -7.342, z center -20.32 with 0.375 Å units. The test ligand with the best binding potential to JAK2 is luteolin, with a binding energy of -8.13, inhibition constant of 1.1, hydrogen bonds on GLN A: 553, SER A: 698, LYS A: 581, GLN A: 626 VAL A: 629, and other bond types on ILE A: 559, LEU A: 579, LEU A: 680.